Effect of different-sized spherical gold nanoparticles grown layer by layer on the sensitivity of an immunochromatographic assay. Issue 31 (10th March 2016) - Li, Juan; Duan, Hong; Xu, Peng; Huang, Xiaolin; Xiong, Yonghua
Abstract : Effect of different-sized spherical gold nanoparticles grown layer by layer on the sensitivity of immunochromatographic assay. Abstract : The immunochromatographic assay (ICA) commonly suffers from low sensitivity because of the insufficient brightness of traditional spherical gold nanoparticles (AuNSs; 20–30 nm). Larger-sized AuNSs exhibit greater potential to improve the detection performance of the ICA method because of their higher molar extinction coefficient. However, oversized AuNSs could produce steric hindrance on the strip. In the present study, the impact of AuNS size on the sensitivity of a competitive ICA method was explored. Four kinds of citrate-stabilized AuNSs with sizes of 20, 60, 100, and 180 nm were synthesized. The affinity properties of four sized AuNS probes toward ochratoxin A and bovine serum albumin conjugates were analyzed using bio-layer interferometry and further characterized by immunological kinetic analysis. These results showed that 100 nm AuNS probes could remarkably enhance the detection signal of the strip due to their higher molar extinction coefficient and stronger affinity to the target antigen. By contrast, 180 nm AuNSs were unsuitable as labeled probes on the strip because of significant steric hindrance. Under the optimal conditions, the 100 nm AuNS-based ICA sensor exhibited the best sensitivity, with a cut-off limit (qualitative detection by naked eye) and half-maximum inhibitory concentration (quantitative analysis by strip reader) in wet (dry) formats 12.5 and 7.15 (10 and 5.3) times better than those of the conventional 20 nm AuNS-based strips, respectively. In summary, 100 nm AuNSs have considerable industrial application potential as alternative novel probe nanomaterials in the competitive ICA platform.